Smoke-free policy and child health - Britton, John (Elsevier, 2017)
On March 24, 2004, Ireland became the first country in the world to implement legislation prohibiting tobacco smoking in workplaces and enclosed public places. The political process leading up to the legislation was long, with opposition from stakeholders with a range of vested interests, particularly the tobacco industry.1 Despite predictions otherwise, the legislation achieved high levels of compliance from the outset, has proved extremely popular, and established a global role model that many countries have now adopted.